2009
DOI: 10.1007/s11064-009-0054-1
|View full text |Cite
|
Sign up to set email alerts
|

BACE and γ-Secretase Characterization and Their Sorting as Therapeutic Targets to Reduce Amyloidogenesis

Abstract: Secretases are named for enzymes processing amyloid precursor protein (APP), a prototypic type-1 membrane protein. This led directly to discovery of novel Aspartyl proteases (beta-secretases or BACE), a tetramer complex gamma-secretase (gamma-SC) containing presenilins, nicastrin, aph-1 and pen-2, and a new role for metalloprotease(s) of the ADAM family as a alpha-secretases. Recent advances in defining pathways that mediate endosomal-lysosomal-autophagic-exosomal trafficking now provide targets for new drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 446 publications
(225 reference statements)
1
34
0
Order By: Relevance
“…As described previously, we detected APP CTFs exclusively in the endosomal fraction of wild-type SHSY5Y (Fig. 3b) (Marks and Berg 2010). Surprisingly, CTF appearance is completely abolished after treatment with the PI3K inhibitor LY294002 (Fig.…”
Section: Pi3-kinase Signaling Regulates Endosomal App Processingsupporting
confidence: 81%
See 1 more Smart Citation
“…As described previously, we detected APP CTFs exclusively in the endosomal fraction of wild-type SHSY5Y (Fig. 3b) (Marks and Berg 2010). Surprisingly, CTF appearance is completely abolished after treatment with the PI3K inhibitor LY294002 (Fig.…”
Section: Pi3-kinase Signaling Regulates Endosomal App Processingsupporting
confidence: 81%
“…These findings suggest that PI3K activated by IRS-2 promotes CTF formation. Previous work indicated that endosomal APP procession is mainly mediated via α-secretase activity (Marks and Berg 2010). Therefore, we analyzed the effect of α-, β-, and γ-secretase inhibitors on endogenous CTF formation and protein abundance of BACE-1, ADAM-10, and TACE in the different membrane fractions (Fig.…”
Section: Pi3-kinase Signaling Regulates Endosomal App Processingmentioning
confidence: 99%
“…166,167) Furthermore, another LXR agonist GW3965 reduced Ab levels and amyloid plaques, enhanced apo E expression, and improved memory deficits in a mouse model of AD (Tg2576). 168) Recently, a relationship has been suggested between SorLA and AD 124,169,170) because SorLA gene variants are associated with sporadic AD. 171) When the AD model mice (APPSwe/PS1DE9) were crossed with SorLA-deficient mice, AD pathology occurred earlier that in the AD model mice expressing SorLA.…”
Section: Lipid Metabolism and Admentioning
confidence: 99%
“…Refi nements include substitution of additional hydrophobic residues to improve passage through the bloodbrain barrier. The search for BACE-1 inhibitors continues, and this enzyme remains a potential target for therapeutic approaches (Vassar et al 2009;Marks and Berg 2010 ;Hunt and Turner 2009;Hills and Vacca 2007 ) .…”
Section: B -Secretase Inhibitorsmentioning
confidence: 99%